2013
DOI: 10.1039/c3bm00012e
|View full text |Cite
|
Sign up to set email alerts
|

Bio-ink properties and printability for extrusion printing living cells

Abstract: Additive biofabrication (3D bioprinting) makes it possible to create scaffolds with precise geometries, control over pore interconnectivity and architectures that are not possible with conventional techniques. Inclusion of cells within the ink to form a "bio-ink" presents the potential to print 3D structures that can be implanted into damaged/diseased tissue to promote highly controlled cell-based regeneration and repair. The properties of an 'ink' are defined by its formulation and critically influence the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
419
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(429 citation statements)
references
References 55 publications
(129 reference statements)
9
419
0
1
Order By: Relevance
“…The latter is more important in real applications of bio-fabrication. For example, Chung's group found that the alginate-gelatin hydrogel had to be printed at low temperatures as the gelation temperature for alginate-gelatin hydrogels is around 11°C [22] . Jia et al evaluated the printability of hydrogel by using a point-to-point strategy to print several dots and found that the plot of dots areas and viscosity can directly shows the relationship between printability and viscosity of different samples.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is more important in real applications of bio-fabrication. For example, Chung's group found that the alginate-gelatin hydrogel had to be printed at low temperatures as the gelation temperature for alginate-gelatin hydrogels is around 11°C [22] . Jia et al evaluated the printability of hydrogel by using a point-to-point strategy to print several dots and found that the plot of dots areas and viscosity can directly shows the relationship between printability and viscosity of different samples.…”
Section: Introductionmentioning
confidence: 99%
“…During conventional rapid solidification-based extrusion, the printing process has been typically investigated based on the effects of ink rheological properties and homogeneity on the printability and the evaluation of printing resolution and accuracy. For example, Chuang et al [19] reported the filament morphology and diameter are closely dependent on the preprocessing of bioinks and their material properties during extrusion printing different sodium alginate (NaAlg)-based solutions. Kang et al [20] printed various alginate, poly(ethylene glycol) diacrylate (PEGDA), and gelatin bioinks under different printing conditions and found that printing conditions including the nozzle diameter, dispensing pressure, path height (standoff distance), path spacing (feed), and printing speed can affect the printing accuracy and resolution of 3D structures.…”
mentioning
confidence: 99%
“…The printing resolution mainly depends on the device characteristics (e.g., nozzle diameter, flow rate, and printing speed), the material properties (e.g., rheological behaviour, wettability, surface tension) and the cell density. Environmental conditions and crosslinking methods also have a critical role on the achievable resolution [17,31,32,111]. Since extrusion bioprinting involves the deposition of cellular bioinks through a small nozzle, printed cells are subjected to mechanical stresses during the process, which may lead to a loss of cell viability and even to alterations in the phenotype [17].…”
Section: Extrusion Bioprintingmentioning
confidence: 99%
“…These studies also demonstrated the possibility to determine and to reduce the shear stresses transmitted to the cells through experimental and numerical studies [17,19,30,46,127]. To address the unique requirements of extrusion bioprinting regarding the print fidelity and biological characteristics, research efforts have been focused on the development of bioinks exhibiting appropriate rheological, mechanical and biological properties [28,32,74,82,100,152,169,174]. A multitude of crosslinking mechanisms, including thermal gelation, ionic and photocrosslinking, have also been explored to induce the in situ gelation of printed materials with the ultimate goal of improving the mechanical properties, the shape fidelity and the formation of interconnected 3D pores throughout the construct [4,28,107], which still remains a major challenge.…”
Section: Extrusion Bioprintingmentioning
confidence: 99%